Development of heat transfer and pressure drop correlations in twisted tube heat exchangers (2020)
Heat transfer in concentric twisted tubes exchangers has several applications in the chemical and food industry mainly due to its compact structure and high transport coefficients, however, its use has been limited as a consequence of drop pressure. This study reports Nusselt number and friction factor correlations as a function of the dimensionless Dean number as well as Prandtl number, and a torsional step parameter. Simulations were carried out using ANSYS CFX® V16.0 software at workstations belonging to Grupo de Investigación en Materiales Avanzados y Energía of Instituto Tecnológico Metropolitano. Six geometries were developed with SolidEdge® ST9 academic license. Geometry modification, cleanup, and repair were made although DesignModeler® 2019 academic license. Finally Meshing® for discretization. The mesh size independence, and incidence of the turbulence model, and twisting step validated the computational tools use. Correlation numerically showed an increase of 60% average respect to smooth bending tube. © Published under licence by IOP Publishing Ltd